Relating Subglacial Water Flow to Surface Velocity Variations of Breiðamerkurjökull, Iceland - Boeckel, Tayo van, 1990- (2015)
The ways in which subglacial hydrology relates to velocity variations of glaciers has been a topic of discussion for several decades. Studies have revealed that changes in sliding, water pressure and water storage do not correlate in phase. In particular, observations have indicated that the overwhelming of the subglacial drainage systems results in increased sliding. Studies have therefore hypothesized that a dynamically evolving subglacial drainage system controls the sliding velocity by adjusting its capacity to variable surface water input. In addition, studies have hypothesized that velocities at the surface are also affected by longitudinal stress gradients caused by spatial variabilities in the drainage system capacities. For this study, GPS data from two locations on Breiðamerkurjökull, Iceland, during 2010, 2012 and 2013, are processed and analyzed. The combination of both hypotheses is tested against the surface velocity measurements. Rain-induced speed-up events indicate that the overwhelming of the drainage system indeed causes rapid acceleration. The drainage system is capable of increasing its capacity within days because a series of rainstorms have decreasing response on glacier acceleration. Sliding velocities are derived after subtracting the ice deformation velocities. These creep velocities are estimated during typical winter weather conditions, when sliding is assumed to be negligible. Velocities calculated with a Full Stokes flowline model support the estimated winter velocities. Basal motion generally peaks in spring and decreases during summer, indicating that the drainage system evolves to greater efficiency during the melt season. Finally, a new conceptual model of the drainage system is presented in an attempt to address the problem of temporal variations of basal motion, water pressure and water storage. The model combines channels, cavities and sheets that dynamically interact on each other.